Effects of potassium hydroxide and aluminum oxide on the performance of a modified solvay process for CO2 capture: A comparative study - Aya A‐H. I. Mourad (14778268) (2023)
In a previous work, the overall performance of modified Solvay process was investigated in the absence of ammonia, where carbon dioxide and brine treatments were accomplished in a single reaction and in the presence of calcium hydroxide (Ca(OH)2). In this study, the impact of alkaline and amphoteric oxides, namely potassium hydroxide (KOH) and aluminum oxide (Al2O3), on the pH level, CO2 capture capacity, ions reduction, and type of produced solids was investigated at a temperature of 20°C and a gas flow rate of 1 L/min. At the stoichiometric ratio and less than the solubility limit, the KOH/brine mixture achieved a CO2 uptake of 0.31 g CO2/g KOH. In comparison, about 0.92 g of CO2 was captured by 1 g of CaO when CaO was added to the brine in an amount that was more than the solubility limit but less than the stoichiometric ratio. Moreover, the percentage of the ions reduction for the KOH and CaO was almost the same except for the sulfate ions, as the best removal was for the CaO. The poorest CO2 capture and ions removal occurred with the Al2O3. X-ray diffraction was used to identify most of the solid products, and the obtained results proved that KOH is a promising alkaline for the combined process. In addition, potassium chloride crystals were produced when KOH was utilized, which is a very valuable product, and it can also be easily separated. Although Al2O3 showed no reactivity, it revealed good results in terms of magnesium ions recovery and could be considered as a coagulant for recovering magnesium ions in the reject brine solution. Other Information Published in: International Journal of Energy Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/er.6737